Applied therapeutics : the clinical use of drugs - Alldredge, Brian K.; Corelli, Robin L.; Ernst, Michael E.; Guglielmo, B. Joseph; Jacobson, Pamala A.; Koda-Kimble, Mary Anne; Kradjan, Wayne A.; Williams, Bradley R. (Lippincott Williams & wilkins, 2013)
This text uses a case-based approach to help students master the fundamentals of drug therapeutics. Students will learn the basics of common diseases and disorders and develop practical problem-solving skills for devising and implementing successful drug treatment regimens. Case studies integrated into each chapter illustrate key concepts and principles of therapeutics and give students practice in developing their own evidence-based therapeutic plans.